Contribution à l’Etude de l’exploitation artisanale des bois d’œuvre dans la ville de Kindu / province du Maniema/RDC - Ir. ADAM ZAKUANI,; Ir.KYANGA KIKUNI Jacques,; lr.LWANGO KAZONI Cedrick,; YAMBA OYULU, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
Our work focused on "contribution to the study of artisanal timber exploitation in the city of Kindu/Maniema/DRC" it had as its general objective: to understand the functioning of the system put in place by the actors of the artisanal wood sector of work. The objectives pursued by this study are to: identify the most exploited species, determine the socio-economic and environmental impacts of artisanal timber harvesting in our environment. The free interview of a pre-established questionnaire on a sample of 120 people grouped together from 3 target markets in the city and the documentary method allowed us to collect some information on artisanal lumber harvesting. Our results show that operators organize themselves to form associations with specific objectives, our respondents exploit more Chlorophora excelsa, Entandrophragma cylindricum, Pericopsis elata, Alstonia Boone, Picnatus angolensis, Rilcinodendron heudelotii, Millicia excelsa and Khaya anthotheca and the latter are endangered in operating area